A comprehensive mechanistic model for simulating algal-bacterial growth dynamics in photobioreactors. (January 2018) - Shriwastav, Amritanshu; Ashok, Vaishali; Thomas, Jeenu; Bose, Purnendu
Highlights: A comprehensive mechanistic model of algal-bacterial growth is developed. The state-of-the-art understanding of algal-bacterial system is incorporated. Model can simulate independent experimental data and complex processes. It can be used for investigating complex relation amongst process variables. Abstract: A comprehensive mechanistic model with state of the art understanding and assumptions is presented to simulate major processes in a photobioreactor for describing the algal-bacterial growth dynamics. The model includes a total of 37 state variables that broadly cover all the essential physiological and physico-chemical processes in such a system. Model parameters are first calibrated with batch experimental data, and thereafter, extensive validation of the model is carried with long term independent experimental data in diverse conditions. The developed model is able to capture the complex system behavior with reasonable accuracy. Also, the comprehensive mathematical formulation with realistic assumptions make this model a valuable tool for gaining better insights into the complex system behavior.